ANOVULATORY INFERTILITY ASSOCIATED WITH THE INSOLVENCY OF THE ENDOMETRIUM - Kurbaniyazova Madina Zafarjanovna; Shonazarova Ugiloy Bakhrom kizi (Scholar Express Journals, 2025)
Female infertility is a very important problem of modern gynecology and reproductive science (the prevalence of female infertility in different countries of the world is 1.5-12%) and is an important interdisciplinary problem. The overall frequency of female infertility as a result of gynecological and extragenital diseases does not decrease below 21%. Objective of the study: to estimate the percentage of infertile women and to conduct a study of the causes of female infertility. Analysis of the obtained data showed that the most common causes of female infertility are: polycystic ovary disease - 25%, anovulatory cycle - 21%; hormonal disorders - 18%; obstruction of the fallopian tubes - 12%; anomalies in the development of the genitourinary system (vaginal atresia, complete or incomplete septum in the uterine cavity, uterine atresia) - 9%; change in the viscosity of cervical mucus - 7%; premature menopause — 2–3%. Conclusions: early diagnosis and timely treatment of gynecological and extragenital diseases can play a significant role in maintaining a woman’s health, but the initial manifestations of these diseases are mostly latent and can only be detected by targeted screening
Keywords: endometrium; female infertility; anovulatory infertility